Simplified Oral Hygiene Index in patients from the Dental Clinic III of Universidad Laica Eloy Alfaro de Manabí in 2023 - Samaniego, Ruth A.; Andrade, Freya M. (Revista Gregoriana de Ciencias de la Salud, 2025)
Biofilm is identified as the primary risk factor for developing oral infections such as caries and periodontal disease. The study aimed to determine the simplified oral hygiene IHOS level in patients who attended Dental Clinic III in the Universidad Laica Eloy Alfaro de Manabí dentistry course period 2023-2. An observational, cross-sectional study was conducted with 273 patients who attended the Dental Clinic III in the ULEAM Dentistry Course period 2023-2. The majority of patients were female (60.1%). The IHOS value was 1.40, distributed in 0.92 for the plaque component and 0.48 for the calculus component. Among patients with good IHOS, 62.7% were female. On the contrary, among those with the IHOS within the lousy category, the proportion was 54.5% for the male gender compared to 45.5% for the female gender.